1979
DOI: 10.1159/000176255
|View full text |Cite
|
Sign up to set email alerts
|

Some Biochemical Observations on Biotin Deficiency in the Rat as a Model for Human Pyruvate Carboxylase Deficiency

Abstract: Biotin deficiency was induced in newborn rats by feeding pregnant rats a biotin-deficient, avidin-rich diet. Signs typical of biotin deficiency are seen as soon as the young rat develops its fur. Deficiency of pyruvate carboxylase (PC) activity in the brains of the young animals (70%) is higher than has been reported before. The highest PC activity is found in the brain stem of control and biotin-deficient rats. Normally fed rats show, shortly after birth, a maximum in liver PC activity, which is absent in bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

1980
1980
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…Under conditions which reduced hepatic pyruvate carboxylase activities to 3% of control, that of cerebrum, brainstem and cerebellum remained at 53 to 71% of control (8). Our data, and those of others on pyruvate carboxylase (9,10) and propionyl CoA carboxylase [EC 6.4.1.3] (9), were consistent with a relative retention of biotin in brains of biotin-deficient rats (11). In the present work, we ask whether there exists a concentrative mechanism for biotin in rat brain.…”
supporting
confidence: 73%
“…Under conditions which reduced hepatic pyruvate carboxylase activities to 3% of control, that of cerebrum, brainstem and cerebellum remained at 53 to 71% of control (8). Our data, and those of others on pyruvate carboxylase (9,10) and propionyl CoA carboxylase [EC 6.4.1.3] (9), were consistent with a relative retention of biotin in brains of biotin-deficient rats (11). In the present work, we ask whether there exists a concentrative mechanism for biotin in rat brain.…”
supporting
confidence: 73%
“…Because of the sensitivity of some flux estimates to the neuronal glutamate concentration, we evaluated the effects of assuming a lower percentage for the fraction of total glutamate in glutamatergic neurons (78%) for P10 cortex where less information is known. In the analysis of the P30 data, anaplerotic flux (V PC ) was assumed to be 20% of glutamine synthesis (V gln ) (Sibson et al, 2001), whereas for the P10 data, V PC was assumed to be 1/4 of its value at P30 (Schrijver et al, 1979). Fitted flow rates included glutamatergic and GABAergic TCA cycle fluxes (V TCA(Glu) , V TCA(GABA) ), astroglial TCA cycle flux (V TCAa ), neurotransmitter cycles (V cyc(Glu/Gln) , V cyc(GABA/Gln) ), GABA shunt flux (V shunt ), and GABAergic TCA cycle flux (V TCA(GABA) ).…”
Section: Determination Of Metabolic Fluxes From Time Course Datamentioning
confidence: 99%
“…This apparent contradiction would appear to be due to the use of egg-white as a source of avidin in the diets of Cunha et al (1946) and other workers, as growth depression has only been noted when egg-white has been included in diets. Tuszynska (1969) and Schrijver et al (1979) showed that biotin supplementation of diets containing egg-white did not result in rat growth equivalent to that observed in animals fed on a laboratory chow of much lower biotin content. This suggested that the growth depression observed when egg-white was given was not entirely due to biotin inadequacy.…”
Section: Discussionmentioning
confidence: 99%